Registeration Portal for Seminar/Workshops - Sandhya Murali, Rushika Verma (International Journal of Scientific Research and Management (IJSRM), 2015)
In a corporate company a trainee or employee requires training for updated knowledge of the latest software’s that have come into the market. For requesting any particular training the employee has to first write an application letter and await for its response which is by all means is a long tedious process. Moreover, it is impossible for the management to keep a track of these application letters knowing the fact that there are so many employees in the company and different departments. For this we propose a paper wherein user (faculty/student) can login and request for a training thereby eliminating a lot of paper work and also view the training sessions made available by the administrator. They can also view their request status after providing the needed request of the seminar. They can also check the availability of the seminar/workshop over a prior period which is updated by the administrator according to the requirements placed by the user.